2021
DOI: 10.1159/000512424
|View full text |Cite
|
Sign up to set email alerts
|

A Double Metachronous Ureter Metastasis following Curative Resection of Rectal Cancer

Abstract: A malignant ureteral obstruction is most often due to primary tumors of the ureter. However, it can occur secondary due to external tumor compression or metastatic infiltration. Distant metastases to the ureter are extremely rare. We present a case of a rare double distant metachronic metastasis to the right ureter as well as to the right renal pelvis in a 58-year-old female with a history of anterior resection for rectal cancer 2 years earlier. She presented with recurrent urinary tract infection and right hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…There is limited evidence or data on locally advanced or metastatic CRC patients with hydronephrosis receiving palliative care. Aghalarov et al (13) reported a case of postoperative recurrence of rectal cancer with urinary tract infection and right-sided hydronephrosis caused by a ureteral mass, who underwent laparoscopic right nephroureterectomy. The resected mass was pathologically confirmed to originate from rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence or data on locally advanced or metastatic CRC patients with hydronephrosis receiving palliative care. Aghalarov et al (13) reported a case of postoperative recurrence of rectal cancer with urinary tract infection and right-sided hydronephrosis caused by a ureteral mass, who underwent laparoscopic right nephroureterectomy. The resected mass was pathologically confirmed to originate from rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 The ureter is an extremely rare location for colorectal metastases. [1][2][3][4][5][6][7][8][9][10] The metastases of the ureter are often associated with extensive metastasis at the time of diagnosis. 8 Although few cases of colon cancer metastasis to the ureter have been reported, our case has 2 significantly different aspects.…”
mentioning
confidence: 99%
“…The most common metastatic sites of colorectal cancer are the lymph node, liver, lung, and bone 1 . The ureter is an extremely rare location for colorectal metastases 1–10 . The metastases of the ureter are often associated with extensive metastasis at the time of diagnosis 8 .…”
mentioning
confidence: 99%